Determination of trace metals in fruit juices - Spirevska, Ilinka; Stojanova, Kornelija (Macedonian Journal of Ecology and Environment, 1994)
A method of square-wave voltamperometry is described for simultaneous determination of Cu and Pb in fruit juices, with acetate buffer and KC1 as supporting electrolyte. The results are in a good agreement with those obtained by the atomic absorption spectroscopic method and VIS spectrophotometry. Also, the elements Fe, Zn, Cd, and Mn in fruit juices are determined by atomic apsorption spectroscopy. The obtained results indicate that the content of all investigated elements in fruit juices is in the permitted value range.